Health impacts of climate-change related natural disasters on persons with disabilities in developing countries: A literature review - Uddin, Taslim; Tasnim, Anika; Islam, Md Redwanul; Islam, Mohammad Tariqul; Salek, A.K.M.; Khan, Md Moniruzzaman; Gosney, James; Haque, M Atiqul (Elsevier Masson SAS, 2024)
Background: Climate change is identified as the foremost health threat in the present era, resulting in a broad range of negative health impacts on individuals, families, and communities. Marginalized populations in developing countries are particularly affected. This literature review explored the health impacts of climate change-related natural disasters on persons with pre-existing physical and mental disabilities in developing countries. Methods: The Joanna Briggs Institute [JBI] evidence synthesis guideline was applied and results were reported following Preferred Reporting Items for Systematic Reviews and Meta-Analyses [PRISMA] guidelines. PubMed, PsycINFO, Scopus, and Embase databases were searched using terms related to ‘persons with disabilities’ (PWD), ‘climate change’, and “developing countries” and types of natural disasters considered to result from climate change. Selected articles were reviewed and thematic analysis was performed. Findings: Fourteen articles were included of which five generalized across multiple countries and nine profiled specific developing countries including Bangladesh, China, Haiti, India, Nepal, Philippines, South Africa, Tuvalu, and Uganda. Five key themes were identified: [i] impact on PWD physical health, [ii] impact on PWD mental health, [iii] resilience and coping strategies of PWD in disasters, [iv] PWD involvement in inclusive disaster planning, and [v] climate-change related natural disasters on PWD in developing countries as a human rights issue. Interpretation: This review underscores the lack of literature related to negative health impacts of climate change-related natural disasters on persons with pre-existing physical and mental disabilities in developing countries. Additional research is required to better understand these impacts as well as contributing social and economic factors and facilitative coping and resilience strategies in climate-related natural disasters. Addressing these gaps can inform development of effective, disability-inclusive disaster management practices which contribute to more equitable climate-change related health and rights-based outcomes for PWD in developing countries.